Robert Brandom - Wanderer, Jeremy (Philosophy now., 2008)
Jeremy Wanderer offers students a clear introduction to the philosophy of Robert Brandom, in particular to his monumental work 'Making It Explicit', one of the most significant (and daunting) works of philosophy of recent years.